The determinants of regional disparities in skill segregation - Evidence from a cross section of German regions - Annekatrin Niebuhr; Javier Revilla Diez; Fabian Böttcher; Friso Schlitte (European Regional Science Association (ERSA), 2010)
Increasing inequality in qualification specific employment prospects characterises labour markets in most highly developed countries. Theoretical models suggest that in-plant skill segregation might matter for the polarization of employment and wages. According to these models production technology and the educational level of the work force are important determinants of skill segregation. There are some studies that investigate the increasing in-plant skill segregation at the national level. However, since production technologies and skill structures are characterized by pronounced regional disparities, there are likely significant differences in the level of segregation between regions. But empirical evidence on corresponding regional inequalities is lacking. The objective of this analysis is to investigate regional disparities in skill segregation in Germany. Moreover, we analyse the determinants of these differences at the regional level. Our findings point to marked disparities among German regions. While rural areas are characterised by a weaker segregation, agglomeration areas have a higher level of skill segregation. Furthermore, skill segregation is increasing in most areas during the period under consideration, which may have regional economic consequences. The results of a regression analysis indicate that the local endowment with human capital is an important determinant for the regional level of skill segregation.
Keywords: 330